Best practices to Teach How to Write Creative Papers with Integrity - Peters, Martine (Canadian Perspectives on Academic Integrity, 2021)
With the abundance of information on the web, university students have difficulties distancing themselves from what they read to produce their own position when writing assignments. Are students taught to write creatively and with integrity while undergraduates at university? This is the research question addressed in this paper. Over three hundred Quebec professors and sessionals were asked what are the best practices they use when teaching their students to produce well written and creative assignments. Results show a wide variety of practices, from teaching informational literacy to giving students very specific guidelines and instructions. Unfortunately, there are still a good number of professors who believe that teaching how to write with integrity is not their responsibility